Growth differentiation factor–15 predicts the prognoses of patients with acute coronary syndrome: a meta-analysis. Issue 1 (December 2016) - Zhang, Shangshi; Dai, Dongjun; Wang, Xian; Zhu, Hongyan; Jin, Hongchuan; Zhao, Ruochi; Jiang, Liting; Lu, Qi; Yi, Fengying; Wan, Xiangxiang; Cui, Hanbin
Abstract Background Recent studies have shown Growth differentiation factor–15 (GDF-15) that is a member of the transforming growth factor β (TGF-β) superfamily might be a potential predictive cytokine for the prognosis of Acute coronary syndrome (ACS). However, there are discrepancies in these studies. Methods Publication searches of the PubMed/Medline and EMBASE databases were performed without any time or ethnicity restrictions. The inclusion and exclusion criteria, when clear, were addressed. Random effects models were used for all analyses. Publication bias was tested using funnel plots and the Egger test. Results We identified eight eligible studies that provided mortality data. Five of these studies provided recurrent myocardial infarction (MI) data. The maximal duration of follow-up ranged from 6 months to 6 years. A significant association was found between the patients with the highest and lowest GDF-15 levels (overall analyses) in terms of mortality (p  < 0.00001; RR = 6.08; 95 % CI = 4.79–7.71) and recurrent MI (p  < 0.00001; RR = 1.76; 95 % CI = 1.49–2.07). We also found significant associations between the subgroup analyses stratified by ACS types, cutoff points and follow-up durations (p  < 0.001). The combined hazard ratio was high for GDF-15 to ACS (HR = 1.656, 95 % CI = 1.467–1.871). Conclusion High plasma GDF-15 levels are associated with an increased risk of mortality and recurrent MI in patients with ACS.